Weil’s Disease dengan Gagal Ginjal Akut - Amelia, Rizki; Fadrian, Fadrian (Faculty of Medicine, Universitas Andalas, 2024)
Weil's disease is a severe leptospirosis characterized by multiorgan failure with symptoms of high fever, jaundice, kidney failure, liver necrosis, lung abnormalities, cardiovascular collapse, neurological changes, and bleeding. Acute kidney injury may occur in 20% to 85% of patients during the second phase of leptospirosis disease. It has been reported a 31-year-old male patient had a persistent high fever, pain in the muscles and joints throughout the body, especially in the muscles of both calves, headache, eyes and the whole body looked yellow, urinating like dark tea. The patient once fished in the river barefoot. Physical examination showed icteric sclera, ciliary injection, and temperature 38.9ºC. Laboratory examination of leukocytes 16,880/mm3, platelets 26,000/mm3, ureum 152 mg/dl, creatinine 6.8 mg/dl, direct bilirubin 15 mg/dl, indirect bilirubin 7.2 mg/dl, SGOT 192 U/L, SGPT 71 U/L. Urinalysis showed hematuria and proteinuria. Anti-leptospira IgM serology showed reactive results. On direct dark field microscopic examination of urine samples, fine spiral-shaped Leptospira bacteria were found. On ultrasound examination of the kidneys, the impression of both kidneys showed acute nephritis. The Modified Faine Criteria Score was 39, which suggests presumptive leptospirosis. The patient was treated with intravenous antibiotics Ceftriaxon 2x1 gram and hemodialysis. Keywords: acute kidney injury, hemodialysis, leptospirosis, Weil’s disease